Conceptual Framework and Analisys of the Business Incubation Process - N. G. Galiyeva (Цифровая трансформация, 2023)
The main stages of the study and analysis of the business incubation process (in the relevant organizations) are presented, both from the perspective of a resident and from the side of a business incubator. The accepted approach to the specifics and characteristics of the leading business incubators / accelerators and other similar organizations from the point of view of project management is explained. In the process of research, a review of academic works and sources of professional associations / institutional organizations was carried out, in which the existing definitions of a business incubator are analyzed, an overview of the organization / business model (business incubator) is provided together with data collection (from interviews and questionnaires). The most famous business incubation programs have been studied. A functional model of a business incubator has been obtained, as well as a set of key performance indicators (KPIs) and metrics that can be useful for a business incubator to achieve effective company management.